Anti‐BCMA Immuno‐NanoPET Radiotracers for Improved Detection of Multiple Myeloma. Issue 2 (7th November 2021) - Thomas, Eloise; Mathieu, Clélia; Moreno‐Gaona, Patricia; Mittelheisser, Vincent; Lux, François; Tillement, Olivier; Pivot, Xavier; Ghoroghchian, Paiman Peter; Detappe, Alexandre
Abstract: Current clinical imaging modalities for the sensitive and specific detection of multiple myeloma (MM) rely on nonspecific imaging contrast agents based on gadolinium chelates for magnetic resonance imaging (MRI) or for 18 F‐FDG‐directed and combined positron emission tomography (PET) and computed tomography (CT) scans. These tracers are not, however, able to detect minute plasma cell populations in the tumor niche, leading to false negative results. Here, a novel PET‐based anti‐BCMA nanoplatform labeled with 64 Cu is developed to improve the monitoring of these cells in both the spine and femur and to compare its sensitivity and specificity to more conventional immunoPET ( 64 Cu labeled anti‐BCMA antibody) and passively targeted PET radiotracers ( 64 CuCl2 and 18 F‐FDG). This proof‐of‐concept preclinical study confirmed that by conjugating up to four times more radioisotopes per antibody with the immuno‐nanoPET platform, an improvement in the sensitivity and in the specificity of PET to detect tumor cells in an orthotopic model of MM is observed when compared to the traditional immunoPET approach. It is anticipated that when combined with tumor biopsy, this immuno‐nanoPET platform may improve the management of patients with MM. Abstract : Current immunoPET radiotracers are limited to 2–4 radioisotopes per monoclonal antibody (mAb). Here, a novel immuno‐nanoPET radiotracer is developed where the mAb is conjugated to three nanoparticles, each presenting four radioisotopes. When conjugated to an anti‐BCMA mAb, this construct enables improved sensitivity and specificity than convention immunoPET approach for multiple myeloma monitoring.